2014
DOI: 10.1177/0034355214558938
|View full text |Cite
|
Sign up to set email alerts
|

Employing People With Disabilities in the Taiwanese Workplace

Abstract: This study aimed to explore the experiences of employers who had long-term experiences with employing people with disabilities in Taiwan. In-depth qualitative interviews were adopted as the main data collection instrument. The participants included 12 Taiwanese employers in the private enterprise sector with 2 or more years of experience hiring employees with disabilities beyond the required employment quota enacted by the Taiwanese government. The results identified four main reasons that led to hiring, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…In contrast to studies of barriers related to inclusion, some studies reported positive expectations of working with persons with disabilities, such as higher loyalty and reliability, and lower turnover (Gröschl, ; Huang & Chen, ). However, Huang and Chen () note that employers hire persons with disabilities to address persistent labor shortages for lower‐level jobs that college‐educated applicants will not take—a positive attitude that points to other persistent problems such as the underemployment of persons with disabilities. It would be helpful to have investigations of a full range of expected future contact and expected outcomes.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast to studies of barriers related to inclusion, some studies reported positive expectations of working with persons with disabilities, such as higher loyalty and reliability, and lower turnover (Gröschl, ; Huang & Chen, ). However, Huang and Chen () note that employers hire persons with disabilities to address persistent labor shortages for lower‐level jobs that college‐educated applicants will not take—a positive attitude that points to other persistent problems such as the underemployment of persons with disabilities. It would be helpful to have investigations of a full range of expected future contact and expected outcomes.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 96%
“…Some employers were concerned about “headaches” (Lengnick‐Hall et al, ) such as more frequent absences or higher government scrutiny associated with hiring persons with disabilities, which increased their fear of discrimination litigation (Jasper & Waldhart, ; Kaye et al, ). A qualitative study of Taiwanese employers by Huang and Chen () found the perceived need for accommodations and extra training and supervision also decreased managers' perceptions of promotability for employees with disabilities.…”
Section: Review Of Empirically Investigated Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is no one type of small business that is unwillingness to hire people with disabilities, employers' hiring decisions are nevertheless often influenced by the types of and severity of disabilities (Huang & Chen, 2015). For instance, people with visual impairments have trouble maintaining, seeking, or even obtaining a job (Unger, Rumrill, & Hennessey, 2005).…”
Section: Negative Attitudesmentioning
confidence: 99%